Have households’ livelihoods and food security rebounded from COVID-19 shocks in Nigeria? Results from a follow-up phone survey - Balana, Bedru; Oyeyemi, Motunrayo; Ogunniyi, Adebayo; Fasoranti, Adetunji; Edeh, Hyacinth O.; Andam, Kwaw S. (International Food Policy Research Institute, 2021)
The effect of the COVID-19 pandemic on households’ income, jobs, and food security have continued despite perceptible reductions in transmission and lifting of restrictive measures in several countries. To assess these effects on Nigerian households, we collected household data in the initial three months after the outbreak of the pandemic (July 2020). To track the changes since the first survey, we conducted a follow-up phone survey with the same households a year later (July 2021). We undertook a comparative analysis between the two surveys focusing on key variables such as income loss, job loss, food security, and dietary diversity. The study also investigated how changes in income, wealth/endowments, social capital, safety net programs, and recurrent conflicts affected the severity of food insecurity amid the pandemic. We found that both income and jobs have rebounded significantly (by 50 percentage points) compared to the baseline results. In terms of food insecurity, households with “severely food insecure” situations dropped from 73 percent in the first survey to 65 percent in the follow-up survey. We also found a 5-percentage point improvement in the household dietary diversity scale in the follow-up survey. However, households reported an increase of more than 70 percent in conflicts or insecurity threats amid the pandemic. This affected farm investment decisions in 44 percent of smallholder farmers surveyed. While income loss significantly worsened households’ food insecurity; livestock ownership and social capital cushioned households from falling into a more severe food insecurity situation. However, safety net programs provided by the government and NGOs did not significantly protect households from falling into severe food insecurity amid the pandemic. We suggest four propositions: prioritize investment in job creation to curb income loss; enable households to build their wealth base (e.g., land tenure security or livestock) to enhance resilience to shocks; revisit targeting approaches of safety net programs to enhance effectiveness of such programs; and finally, devise and implement conflict resolutions to induce investment and enhance productivity.